الطريقة التكاملية في تعليم اللغة - خلفاوي, فريد; مالكية, بلقاسم (University of Eloued جامعة الوادي, 2016)
يتناول هذا المقال إشكالية هامة في تعليم اللغات خاصة اللغة العربية، هي الطريقة التكاملية في تعليمها، فلكي يكون هذا التعلّم ناجعا، حيث يكتسب المتعلم اللغة بشكل صحيح، لابد من اختيار الطريقة المثلى في تعليمه إيّاها، ونظرا لأن الطريقة عنصر أساس في العملية التعليمية التعلّمية، فإن عملية التعلّم تتوقف على مدى نجاعتها وفاعليتها، فبالنظر للغة على أنها كل متكامل وفق المنظور اللساني الحديث، ينبغي تعليمها وفق طريقة تراعي هذا التكامل اللغوي، من هنا سميت هذه الطريقة المقصودة بالتكاملية، كما يطلق عليها في عرف المقاربات اسم المقاربة النصية إن هذه الدراسة تعالج هذه الإشكالية فتتعرض إلى مفهومها وخصائصها وأهميتها والأهداف التي تروم تحقيقها،وتبيّن البيداغوجيات المستعملة في تطبيقها، وجدلية ظهورها مع التطورات التربوية الحديثة، وتبيان جذورها الأولى في تعليم اللغة العربية، لنخلص في الأخير إلى نجاعة تعليم هذه اللغة وفق هذه الطريقة من عدمها This article addressesan importantproblematicinteaching languages, especially in Arabiclanguage, WhichIs the perfect mannertoteach it, to be effective, learning where a learner acquires the language correctly , you must choose how best to teach it , Because themethodis an essential elementinthe educational and learning process, that the learning process depends on the extent of its efficacy and its effectiveness, given to language as a whole in accordance with themodern lingual perspective , should be taught in a manner which takes into account the linguistic integration, here This intended method is called" the integration",as it's called in custom approaches as "textualapproach". This study treats this problematic, exposed to its concept, its characteristics and its Importance and the objectives that aim to achieve, and indicate the used pedagogies in the application, and the dialectic of appearance with modern educational developments, and to indicate the first roots in teaching the Arabic language, finally we conclude to the efficacy of teaching this language in this way or not .
Keywords: تعلم اللغات، التكاملية، المقاربة النصية; Learning languages, integration, textualapproach